Graphene composite perovskite manganese oxide polycrystalline ceramic as well as preparation method and application thereof
By introducing graphene into the grain boundaries of ABO3 perovskite manganese oxide polycrystalline ceramics, the problem of limited sensitivity of perovskite manganese oxide under room temperature conditions is solved, and the high conductivity and excellent room temperature working performance of polycrystalline ceramics are achieved.
Patent Information
- Application Number
- CN202411769440.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
ABO3 perovskite manganese oxide has defects and impurities at the grain boundaries, which affects its electrical transport performance, resulting in poor TCR and Tk regulation effects, limiting its high sensitivity application under room temperature conditions.
Graphene composite perovskite manganese oxide polycrystalline ceramics are used to prepare composite powders by tip ultrasonic ball milling. Discharge plasma sintering technology is used to distribute graphene nanosheets in the grain boundaries of the ceramic to improve the grain boundary effect and enhance carrier migration efficiency.
It significantly improves the conductivity of polycrystalline ceramics, improves the TCR value, and brings the Tk value to close to 300K, achieving excellent room temperature working performance, is suitable for non-refrigerated infrared detectors, and improves detection accuracy.
Smart Images

Figure CN119569453A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of non-refrigerated high-sensitivity infrared detection, and relates to a graphene composite perovskite manganese oxide polycrystalline ceramic and a preparation method and application thereof. Background Art
[0002] Uncooled infrared detectors use the unique thermal effect of infrared radiation to convert infrared radiation into heat first, and then convert the heat into electrical signals through sensitive materials. Therefore, the sensitivity of the sensitive materials of uncooled infrared detectors to temperature changes directly affects the detection accuracy of uncooled infrared detectors, and the sensitivity of sensitive materials to temperature changes can be characterized by the temperature coefficient of resistivity (TCR). The larger the TCR, the more significant the resistance change of the sensitive materials when the temperature changes, that is, the larger the TCR, the greater the sensitivity of the sensitive materials to temperature changes, and the higher the detection accuracy of the uncooled infrared detector. At the same time, uncooled infrared detectors are mostly used at room temperature. The main difference between uncooled infrared detectors and cooled infrared detectors is that uncooled infrared detectors can be used without cooling. The peak temperature TCR of TCR is k Equivalent to the temperature at which the sensitive element material can work, T k The closer the value is to room temperature, the better the room temperature working performance of the sensitive element material is. Therefore, the TCR value of the sensitive element material is improved and its T k The value is closer to room temperature, which can make the sensitive element material more adaptable to room temperature operation and have a higher sensitivity to temperature changes. Therefore, when the sensitive element material is applied to the uncooled infrared detector, the uncooled infrared detector has a higher detection accuracy, which is of great significance.
[0003] At present, perovskite manganese oxides are mainly divided into two types: ABO3 type and A2BO4 type. The two types of perovskite manganese oxides have significant differences in structure. The perovskite manganese oxide of the present invention belongs to the ABO3 type. Due to the defects and impurities at the grain boundaries of the ABO3 type perovskite manganese oxide, its electrical transport performance is affected, resulting in a higher resistivity at the grain boundaries. When the carriers pass through these areas, they will be disturbed by the scattering effect, which reduces the mobility of the itinerant electrons, resulting in the ABO3 type perovskite manganese oxide having a poor performance on TCR and T k The control effect is limited, and the high sensitivity of polycrystalline ceramics to temperature changes at room temperature cannot be effectively exerted, affecting the detection accuracy of uncooled infrared detectors.
[0004] Therefore, it is necessary to provide a graphene composite perovskite manganese oxide polycrystalline ceramic and its preparation method and application, so as to improve the TCR value of polycrystalline ceramic and make its T k The value is closer to room temperature. Summary of the invention
[0005] In order to overcome the problems in the background technology, the present invention adopts the cutting-edge ultrasonic plus ball milling method to prepare the composite powder, and the graphene composite perovskite manganese oxide polycrystalline ceramic prepared by the spark plasma sintering technology. The graphene nanosheets are distributed in the grain boundaries of the polycrystalline ceramic, and the existence form of graphene in the ceramic is mainly grain boundary enrichment, which effectively improves the grain boundary effect of the polycrystalline ceramic, enhances the efficiency of carrier migration between grains, and significantly improves the conductive performance of the polycrystalline ceramic, thereby improving the TCR value of the polycrystalline ceramic, and the polycrystalline ceramic T k The value is close to 300K, which makes the polycrystalline ceramics of the present invention have excellent room temperature working performance.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] On the one hand, the present invention provides a graphene composite perovskite manganese oxide polycrystalline ceramic, in which graphene nanosheets are distributed in the grain boundaries of the perovskite manganese oxide ceramic, and the chemical expression of the graphene composite perovskite manganese oxide polycrystalline ceramic is:
[0008] La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y , wherein G is graphene, y is the mass fraction of graphene in the perovskite manganese oxide composite powder, and y=0.1-0.2%.
[0009] Another aspect of the present invention provides a method for preparing the above-mentioned graphene composite perovskite manganese oxide polycrystalline ceramic, the preparation method comprising the following steps:
[0010] (1) The raw materials La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O were weighed according to the stoichiometric ratio and La was prepared by the sol-gel method. 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder;
[0011] (2) adding graphene to isopropanol and subjecting it to a tip ultrasonic treatment to obtain a graphene dispersion solution, and then adding the La obtained in step (1) to the 0.81 (Ca 0.03 Sr 0.16 ) adding MnO3 precursor powder to a graphene dispersion solution, and simultaneously adding an anionic surfactant to obtain a mixed solution;
[0012] (3) The mixed solution obtained in step (2) is subjected to tip ultrasonic treatment, ball milling, and drying in sequence to obtain La 0.81 (Ca 0.03Sr 0.16 )MnO3:G y Composite powder;
[0013] (4) Under an inert gas pressurized environment, the La obtained in step (3) 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y The composite powder is subjected to spark plasma sintering (SPS) to obtain graphene composite perovskite manganese oxide polycrystalline ceramics.
[0014] Preferably, in step (2), the amount of isopropanol used is about the same as La 0.81 (Ca 0.03 Sr 0.16 )The liquid-to-solid ratio of the MnO3 precursor powder is 10mL:3g.
[0015] Preferably, the anionic surfactant is sodium dodecyl sulfate, and the sodium dodecyl sulfate and La 0.81 (Ca 0.03 Sr 0.16 )The mass ratio of MnO3 precursor powder is 1:20.
[0016] Preferably, in steps (2) and (3), the tip ultrasonic treatment frequency is 25 kHz, and the treatment is carried out for 15 s at an amplitude of 10 μm, and then stopped for 25 s, and the cycle is repeated for a total of 3 hours; in step (3), the ball milling speed is 300 rpm, the ball milling medium is isopropanol, the ball-to-material ratio is 2:1 to 5:1, and the ball milling time is 3 hours; the drying temperature is 55°C, and the drying time is 50 minutes.
[0017] Preferably, in step (4), the inert gas is argon and the ambient pressure is 3-6.5 Pa.
[0018] Preferably, the spark plasma sintering process is as follows: firstly, the temperature is raised to 800°C at a heating rate of 100°C / min, then the temperature is raised to 900-1500°C at a heating rate of 40°C / min, kept at that temperature for 10-20min, then the temperature is lowered to 600°C at a cooling rate of 50°C / min, and then La is allowed to 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y The composite powder is cooled to room temperature in the furnace.
[0019] Preferably, in step (1), La is prepared by sol-gel method. 0.81 (Ca 0.03 Sr 0.16)MnO3 precursor powder is prepared as follows: La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O are weighed as raw materials according to the stoichiometric ratio, and citric acid is weighed according to the molar ratio of the raw materials to citric acid, raw material: citric acid = 1:2, and then the raw materials and citric acid are dissolved in deionized water, and then ethylene glycol is added according to the molar ratio of citric acid to ethylene glycol, citric acid: ethylene glycol = 1:4, to obtain a mixed solution; the mixed solution is stirred and heated for 2 hours, and a wet sol is formed when the mixed liquid becomes viscous and accompanied by foaming, and the wet gel is dried at 200°C for 12 hours to completely evaporate the water to obtain a dry gel; after grinding the dry gel for 30 minutes, it is pre-sintered at 500°C for 10 hours to obtain La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0020] Preferably, the graphene has a purity of 99.9% and a specific surface area of 120 to 150 m 2 / g, the average flake thickness is 5 to 8 nm, and the average particle size is 5 to 10 μm.
[0021] The present invention also proposes the application of the above graphene composite perovskite manganese oxide polycrystalline ceramic in an uncooled infrared detector.
[0022] Beneficial effects of the present invention:
[0023] 1. The graphene of the present invention enters La as a second phase 0.81 (Ca 0.03 Sr 0.16 )MnO3 ceramics, and its existence form in ceramics is mainly grain boundary enrichment. Graphene can form conductive channels at grain boundaries, which is beneficial to electron conduction, improves the charge transfer behavior at grain boundaries, improves the grain boundary effect of polycrystalline ceramics, passivates the defect states at grain boundaries, induces improvement of the crystallization quality of polycrystalline ceramics, enhances the carrier migration efficiency between grains, and significantly improves the conductive properties of polycrystalline ceramics, thereby improving the TCR value of polycrystalline ceramics.
[0024] 2. The present invention generates high-frequency vibration and shear force through cutting-edge ultrasonic treatment, which can effectively break the agglomeration between graphene and disperse it into the solvent. At the same time, with the help of anionic surfactants and ball milling, the bonding between graphene and La is strengthened. 0.81 (Ca 0.03 Sr 0.16 )The dispersion and mixing uniformity of MnO3 precursor powder are improved to prepare a more uniform composite polycrystalline ceramic.
[0025] 3. The present invention generates high-frequency vibration and shear force through the tip ultrasonic treatment, so that
[0026] La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder can obtain finer grains, thereby producing more grain boundaries and providing more space for graphene to fill the gaps, which is beneficial to enhance the electron transmission effect and improve the electrical transport performance of polycrystalline ceramics.
[0027] 4. The present invention can effectively reduce the sintering time by spark plasma sintering (SPS), avoid graphene oxidation and overburning caused by stress generated by uneven thermal expansion, and at the same time, it is beneficial to enhance the bonding between graphene and La. 0.81 (Ca 0.03 Sr 0.16 )MnO3, reducing defects and pores at the interface, and helping to improve the TCR value of polycrystalline ceramics.
[0028] 5. The present invention can effectively reduce dislocations at grain boundaries, reduce scattering effects, and improve electron mobility by performing SPS, which is conducive to obtaining a larger TCR value.
[0029] 6. The present invention can concentrate high-energy pulse energy at the grain boundaries by performing SPS, which is beneficial to the precise filling and dispersion of graphene at the grain boundaries, and helps the graphene to preferentially arrange at the grain boundaries to obtain the best electronic conduction effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 La is the composite of graphene grain boundaries 0.81 (Ca 0.03 Sr 0.16 ) Schematic diagram of MnO3 ceramics;
[0031] Figure 2 The SEM surface morphology images of the polycrystalline ceramics prepared in Example 1 of the present invention, wherein (a) is a SEM surface morphology image of the polycrystalline ceramics with a scale of 3 μm, and (b) is a SEM surface morphology image of the polycrystalline ceramics with a scale of 10 μm;
[0032] Figure 3 The ρ-T curve and TCR-T curve of the polycrystalline ceramic prepared in Example 1, wherein (a) is the ρ-T curve and (b) is the ρ-T curve;
[0033] Figure 4 The ρ-T curve and TCR-T curve of the polycrystalline ceramic prepared in Example 2, wherein (a) is the ρ-T curve and (b) is the ρ-T curve;
[0034] Figure 5 The ρ-T curve and TCR-T curve of the polycrystalline ceramic prepared in Example 3, wherein (a) is the ρ-T curve and (b) is the ρ-T curve;
[0035] Figure 6 These are the ρ-T curve and TCR-T curve of the polycrystalline ceramics prepared in Example 4, where (a) is the ρ-T curve and (b) is the ρ-T curve. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with specific embodiments.
[0037] Embodiment 1:
[0038] In this embodiment, polycrystalline ceramics are prepared by the following method:
[0039] (1) Accurately weigh 9.2512 g La(NO3)3·6H2O (purity ≥ 99.0%), 0.8852 g Sr(NO3)2 (purity ≥ 99.0%), 0.1861 g Ca(NO3)2 (purity ≥ 99.0%) and 9.3094 g Mn(NO3)2·4H2O (purity = 50.0%), and 21.9738 g citric acid (chelating agent) and dissolve them in deionized water, and then add 8 mL of ethylene glycol (gelling agent) to obtain a mixed solution. The mixed solution is stirred and heated for 2 h. When the liquid is relatively viscous and accompanied by foaming, a wet sol is formed. The wet gel is placed in a drying oven and dried at 200°C for 12 h to completely evaporate the water to obtain a dry gel. The dry gel was fully ground in a mortar for 30 min, and then placed in a box furnace and pre-sintered at 500 °C for 10 h to obtain 6gLa 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0040] (2) 0.0072 g of graphene was added to 20 mL of isopropanol (y = 0.12%), and the tip was first ultrasonically treated for 15 s at a frequency of 25 kHz and an amplitude of 10 μm, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h to obtain a graphene dispersion solution.
[0041] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is added to the graphene dispersion solution, and La 0.81 (Ca 0.03 Sr 0.16 )MnO3 and graphene mixed solution, and 0.3g sodium dodecyl sulfate was added to prevent graphene agglomeration.
[0042] (4) The mixed solution was first subjected to tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm for 15 s, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h. The mixed solution was then blended with isopropanol medium in a planetary ball mill at a speed of 300 rpm for 3 h. The ball-to-material ratio during ball milling was 3:1.
[0043] (5) In order to evaporate and remove excess alcohol and sodium dodecyl sulfate, the mixed solution after ball milling in step (4) was placed in a rotary evaporator and dried at 55° C. for 50 min to obtain
[0044] La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.12 Composite powder.
[0045] (6) For La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.12 The powder was sintered using SPS. First, argon was filled into the sintering furnace until the pressure inside the furnace reached 5 Pa. Then, the sintering furnace was set to heat up to 800 °C at a heating rate of 100 °C / min, and then to 900 °C at a heating rate of 40 °C / min. After keeping the temperature for 10 minutes, the temperature was lowered to 600 °C at a cooling rate of 50 °C / min, and then cooled to room temperature with the furnace. Finally, L-shaped 20 mm in diameter and 8 mm in thickness were obtained. a0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.12 Polycrystalline ceramic block.
[0046] The polycrystalline ceramic block prepared in this example was subjected to a scanning electron microscope experiment, and the results were as follows: Figure 2 As shown, the resistivity ρ of the polycrystalline ceramic block prepared in this embodiment is tested, and the TCR value is obtained by calculation. The result is as follows Figure 3 As shown, through Figure 2 It can be seen that the polycrystalline ceramic block prepared in this embodiment has a high degree of ceramic densification, good grain growth, uniform size, regular morphology, good connectivity, no abnormal growth phenomenon was observed, and no other phases were observed.
[0047] pass Figure 3 It can be seen that the TCR value of the polycrystalline ceramic block prepared in this embodiment reaches 18.51% / K; k It reaches 303.28K, which is within the room temperature range.
[0048] Embodiment 2:
[0049] In this embodiment, polycrystalline ceramics are prepared by the following method:
[0050] (1) This example uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0051] (2) 0.0084 g of graphene was added to 20 mL of isopropanol (y = 0.14%), and the tip was first ultrasonically treated for 15 s at a frequency of 25 kHz and an amplitude of 10 μm, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h to obtain a graphene dispersion solution.
[0052] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is added to the graphene dispersion solution, and La 0.81 (Ca 0.03 Sr 0.16 )MnO3 and graphene mixed solution, and 0.3g sodium dodecyl sulfate was added to prevent graphene agglomeration.
[0053] (4) The mixed solution was first subjected to tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm for 15 s, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h. The mixed solution was then blended with isopropanol medium in a planetary ball mill at a speed of 300 rpm for 3 h. The ball-to-material ratio during ball milling was 2:1.
[0054] (5) In order to evaporate and remove excess alcohol and sodium dodecyl sulfate, the mixed solution after ball milling in step (4) was placed in a rotary evaporator and dried at 55° C. for 50 min to obtain
[0055] La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.14 Composite powder.
[0056] (6) For La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.14The powder was sintered using SPS. First, argon was filled into the sintering furnace until the pressure inside the furnace reached 3 Pa. Then, the sintering furnace was set to heat up to 800 °C at a heating rate of 100 °C / min, and then to 1100 °C at a heating rate of 40 °C / min. After keeping the temperature for 12 minutes, the temperature was lowered to 600 °C at a cooling rate of 50 °C / min, and then cooled to room temperature with the furnace. Finally, L-shaped 20 mm in diameter and 8 mm in thickness were obtained. a0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.14 Polycrystalline ceramic block.
[0057] The resistivity ρ of the polycrystalline ceramic block prepared in this embodiment is tested, and the TCR value is obtained by calculation. The result is as follows: Figure 4 shown.
[0058] pass Figure 4 It can be seen that the TCR value of the polycrystalline ceramic prepared in this embodiment reaches 25.25% / K; k The temperature reaches 299.97 K, which is within the room temperature range. The grain morphology and growth morphology of the perovskite manganese oxide polycrystalline ceramic are similar to those in Example 1.
[0059] Embodiment 3:
[0060] (1) This example uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0061] (2) 0.0096 g of graphene was added to 20 mL of isopropanol (y = 0.16%), and tip ultrasonic treatment was performed for 15 s at a frequency of 25 kHz and an amplitude of 10 μm, followed by a 25 s stop, followed by another 15 s tip ultrasonic treatment, followed by a 25 s stop, and this cycle was repeated for a total of 3 h to obtain a graphene dispersion solution.
[0062] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is added to the graphene dispersion solution, and La 0.81 (Ca 0.03 Sr 0.16 )MnO3 and graphene mixed solution, and 0.3g sodium dodecyl sulfate was added to prevent graphene agglomeration.
[0063] (4) The mixed solution was first subjected to tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm for 15 s, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h. The mixed solution was then blended with isopropanol medium in a planetary ball mill at a speed of 300 rpm for 3 h. The ball-to-material ratio during ball milling was 5:1.
[0064] (5) In order to evaporate and remove excess alcohol and sodium dodecyl sulfate, the mixed solution after ball milling in step (4) was placed in a rotary evaporator and dried at 55° C. for 50 min to obtain
[0065] La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.16 Composite powder.
[0066] (6) For La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.16 The powder was sintered using SPS. First, argon was filled into the sintering furnace until the pressure inside the furnace reached 6.5 Pa. Then, the sintering furnace was set to heat up to 800°C at a heating rate of 100°C / min, and then to 1200°C at a heating rate of 40°C / min. After keeping the temperature for 15 minutes, the temperature was lowered to 600°C at a cooling rate of 50°C / min, and then cooled to room temperature with the furnace. Finally, L-shaped 20 mm in diameter and 8 mm in thickness were obtained. a0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.16 Polycrystalline ceramic block.
[0067] The resistivity ρ of the polycrystalline ceramic block prepared in this embodiment is tested, and the TCR value is obtained by calculation. The result is as follows: Figure 5 shown.
[0068] pass Figure 5 It can be seen that the TCR value of the polycrystalline ceramic prepared in this embodiment reaches 33.58% / K; k The temperature reaches 298.65 K, which is within the room temperature range. The grain morphology and growth morphology of the perovskite manganese oxide polycrystalline ceramic are similar to those in Example 1.
[0069] Embodiment 4:
[0070] (1) This example uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0071] (2) 0.0108 g of graphene was added to 20 mL of isopropanol (y = 0.18%), and the tip was first ultrasonically treated for 15 s at a frequency of 25 kHz and an amplitude of 10 μm, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h to obtain a graphene dispersion solution.
[0072] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is added to the graphene dispersion solution, and La 0.81 (Ca 0.03 Sr 0.16 )MnO3 and graphene mixed solution, and 0.3g sodium dodecyl sulfate was added to prevent graphene agglomeration.
[0073] (4) The mixed solution was first subjected to tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm for 15 s, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h. The mixed solution was then blended with isopropanol medium in a planetary ball mill at a speed of 300 rpm for 3 h. The ball-to-material ratio during ball milling was 3:1.
[0074] (5) In order to evaporate and remove excess alcohol and sodium dodecyl sulfate, the mixed solution after ball milling in step (4) was placed in a rotary evaporator and dried at 55° C. for 50 min to obtain
[0075] La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.18 Composite powder.
[0076] (6) For La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.18 The powder was sintered using SPS. First, argon was filled into the sintering furnace until the pressure inside the furnace reached 5 Pa. Then, the sintering furnace was set to heat up to 800 °C at a heating rate of 100 °C / min, and then to 1300 °C at a heating rate of 40 °C / min. After keeping the temperature for 18 minutes, the temperature was lowered to 600 °C at a cooling rate of 50 °C / min, and then cooled to room temperature with the furnace. Finally, L-shaped 20 mm in diameter and 8 mm in thickness were obtained. a0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.18 Polycrystalline ceramic block.
[0077] The resistivity ρ of the polycrystalline ceramic block prepared in this embodiment is tested, and the TCR value is obtained by calculation. The result is as follows: Figure 6 shown.
[0078] pass Figure 6 It can be seen that the TCR value of the polycrystalline ceramic prepared in this embodiment reaches 26.97% / K; k The temperature reaches 295.15 K, which is within the room temperature range. The grain morphology and growth morphology of the perovskite manganese oxide polycrystalline ceramic are similar to those in Example 1.
[0079] Example 5
[0080] (1) This example uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0081] (2) 0.012 g of graphene was added to 20 mL of isopropanol (y = 0.2%), and the tip was first ultrasonically treated for 15 s at a frequency of 25 kHz and an amplitude of 10 μm, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h to obtain a graphene dispersion solution.
[0082] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is added to the graphene dispersion solution, and La 0.81 (Ca 0.03 Sr 0.16 )MnO3 and graphene mixed solution, and 0.3g sodium dodecyl sulfate was added to prevent graphene agglomeration.
[0083] (4) The mixed solution was first subjected to tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm for 15 s, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h. The mixed solution was then blended with isopropanol medium in a planetary ball mill at a speed of 300 rpm for 3 h. The ball-to-material ratio during ball milling was 3:1.
[0084] (5) In order to evaporate and remove excess alcohol and sodium dodecyl sulfate, the mixed solution after ball milling in step (4) was placed in a rotary evaporator and dried at 55° C. for 50 min to obtain
[0085] La 0.81 (Ca 0.03 Sr 0.16)MnO3:G 0.2 Composite powder.
[0086] (6) For La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.2 The powder was sintered using SPS. First, argon was filled into the sintering furnace until the pressure inside the furnace reached 3 Pa. Then, the sintering furnace was set to heat up to 800 °C at a heating rate of 100 °C / min, and then to 1500 °C at a heating rate of 40 °C / min. After keeping the temperature for 20 minutes, the temperature was lowered to 600 °C at a cooling rate of 50 °C / min, and then cooled to room temperature with the furnace. Finally, L-shaped 20 mm diameter and 8 mm thickness were obtained. a0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.2 Polycrystalline ceramic block.
[0087] The polycrystalline ceramics prepared in this embodiment have similar properties to those of Embodiment 4.
[0088] Example 6
[0089] (1) This example uses the same method as in Example 1 to prepare La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
[0090] (2) 0.006 g of graphene was added to 20 mL of isopropanol (y = 0.1%), and the tip was first ultrasonically treated for 15 s at a frequency of 25 kHz and an amplitude of 10 μm, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h to obtain a graphene dispersion solution.
[0091] (3) The La prepared in step (1) 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is added to the graphene dispersion solution, and La 0.81 (Ca 0.03 Sr 0.16 )MnO3 and graphene mixed solution, and 0.3g sodium dodecyl sulfate was added to prevent graphene agglomeration.
[0092] (4) The mixed solution was first subjected to tip ultrasonic treatment at a frequency of 25 kHz and an amplitude of 10 μm for 15 s, then stopped for 25 s, then subjected to tip ultrasonic treatment for another 15 s, and then stopped for 25 s, and this cycle was repeated for a total of 3 h. The mixed solution was then blended with isopropanol medium in a planetary ball mill at a speed of 300 rpm for 3 h. The ball-to-material ratio during ball milling was 2:1.
[0093] (5) In order to evaporate and remove excess alcohol and sodium dodecyl sulfate, the mixed solution after ball milling in step (4) was placed in a rotary evaporator and dried at 55° C. for 50 min to obtain
[0094] La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.14 Composite powder.
[0095] (6) For La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.14 The powder was sintered using SPS. First, argon was filled into the sintering furnace until the pressure inside the furnace reached 3 Pa. Then, the sintering furnace was set to heat up to 800 °C at a heating rate of 100 °C / min, and then to 1100 °C at a heating rate of 40 °C / min. After keeping the temperature for 12 minutes, the temperature was lowered to 600 °C at a cooling rate of 50 °C / min, and then cooled to room temperature with the furnace. Finally, L-shaped 20 mm in diameter and 8 mm in thickness were obtained. a0.81 (Ca 0.03 Sr 0.16 )MnO3:G 0.14 Polycrystalline ceramic block.
[0096] The polycrystalline ceramics prepared in this embodiment have similar properties to those prepared in embodiment 1.
[0097] By Example 2 ( Figure 4 ) and Example 1 ( Figure 3 ) comparison shows that when the doping amount increases, the peak resistivity of polycrystalline ceramics decreases, which is related to the improvement of the connectivity between grains by graphene through grain boundary recombination. At the same time, the TCR value of polycrystalline ceramics increases, mainly because the grain boundary scattering effect, electron-electron scattering, electron-phonon scattering and electron-magnon scattering are improved.
[0098] The TCR value of the polycrystalline ceramic prepared in Example 3 exceeds 30% / K and reaches 33.58% / K. k It is also near room temperature (298.65K), indicating that the polycrystalline ceramics of the present invention can effectively improve the grain boundary effect of polycrystalline ceramics, passivate the defect states at the grain boundaries, and induce the improvement of La 0.81(Ca 0.03 Sr 0.16 )The crystal quality of MnO3 materials is improved, and the carrier transport behavior between grains is enhanced, thereby greatly improving the electrical transport performance of the composite material.
[0099] The peak resistivity of the polycrystalline ceramic prepared in Example 4 is slightly increased, and the TCR value is slightly decreased, but still exceeds 20% / K. This is because when too much graphene is doped, the graphene agglomerates will form larger aggregates, which may destroy the conductive network in the polycrystalline ceramic, reduce the effective conductive path, and increase the resistivity. This shows that the graphene doping amount cannot be too large. When the graphene doping amount of the present invention is the largest, although it will cause a certain negative impact on the performance of the polycrystalline ceramic, the impact is small and is within the normal use range.
[0100] In summary, the polycrystalline ceramics prepared by the present invention have a high TCR value, and T k The value is close to 300K, which proves that the polycrystalline ceramic of the present invention has a high sensitivity to temperature changes at room temperature. Using it in an uncooled infrared detector can effectively improve the detection accuracy of the uncooled infrared detector.
[0101] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A graphene composite perovskite manganese oxide polycrystalline ceramic, characterized in that: In the graphene composite perovskite manganese oxide polycrystalline ceramic, graphene nanosheets are distributed in the grain boundaries of the perovskite manganese oxide ceramic, and the chemical expression of the graphene composite perovskite manganese oxide polycrystalline ceramic is La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y , wherein G is graphene, y is the mass fraction of graphene in the perovskite manganese oxide powder, and y=0.1 to 0.2%.
2. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 1, characterized in that: The preparation method comprises the following steps: (1) The raw materials La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O were weighed according to the stoichiometric ratio and La was prepared by the sol-gel method. 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder; (2) adding graphene to isopropanol and subjecting it to a tip ultrasonic treatment to obtain a graphene dispersion solution, and then adding the La obtained in step (1) to the 0.81 (Ca 0.03 Sr 0.16 ) adding MnO3 precursor powder to a graphene dispersion solution, and simultaneously adding an anionic surfactant to obtain a mixed solution; (3) The mixed solution obtained in step (2) is subjected to tip ultrasonic treatment, ball milling, and drying in sequence to obtain La 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y Composite powder; (4) Under an inert gas pressurized environment, the La obtained in step (3) 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y The composite powder is subjected to spark plasma sintering to obtain graphene composite perovskite manganese oxide polycrystalline ceramics.
3. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In the step (2), the amount of isopropanol used is equal to La 0.81 (Ca 0.03 Sr 0.16 )The liquid-to-solid ratio of the MnO3 precursor powder is 10mL:3g.
4. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: The anionic surfactant is sodium dodecyl sulfate, and the sodium dodecyl sulfate and La 0.81 (Ca 0.03 Sr 0.16 )The mass ratio of MnO3 precursor powder is sodium dodecyl sulfate:La 0.81 (Ca 0.03 Sr 0.16 )MnO3=1:
20.
5. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In the steps (2) and (3), the tip ultrasonic treatment frequency is 25kHz, and the treatment is carried out for 15s at an amplitude of 10μm, and then stopped for 25s, and the cycle is repeated for a total of 3h; in the step (3), the ball milling speed is 300rpm, the ball milling medium is isopropanol, the ball-to-material ratio is 2:1 to 5:1, and the ball milling time is 3h; the drying temperature is 55°C, and the drying time is 50min.
6. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In the step (4), the inert gas is argon and the ambient pressure is 3-6.5 Pa.
7. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: The spark plasma sintering process is as follows: firstly, the temperature is raised to 800°C at a heating rate of 100°C / min, then the temperature is raised to 900-1500°C at a heating rate of 40°C / min, kept at this temperature for 10-20min, then the temperature is lowered to 600°C at a cooling rate of 50°C / min, and then La is allowed to 0.81 (Ca 0.03 Sr 0.16 )MnO3:G y The composite powder is cooled to room temperature in the furnace.
8. The method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 2, characterized in that: In the step (1), La is prepared by sol-gel method. 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder is prepared as follows: La(NO3)3·6H2O, Sr(NO3)2, Ca(NO3)2 and Mn(NO3)2·4H2O are weighed as raw materials according to the stoichiometric ratio, and citric acid is weighed according to the molar ratio of the raw materials to citric acid, raw material: citric acid = 1:2, and then the raw materials and citric acid are dissolved in deionized water, and then ethylene glycol is added according to the molar ratio of citric acid to ethylene glycol, citric acid: ethylene glycol = 1:4, to obtain a mixed solution; the mixed solution is stirred and heated for 2 hours, and a wet sol is formed when the mixed liquid becomes viscous and accompanied by foaming, and the wet gel is dried at 200°C for 12 hours to completely evaporate the water to obtain a dry gel; after grinding the dry gel for 30 minutes, it is pre-sintered at 500°C for 10 hours to obtain La 0.81 (Ca 0.03 Sr 0.16 )MnO3 precursor powder.
9. A method for preparing a graphene composite perovskite manganese oxide polycrystalline ceramic according to any one of claims 2 to 8, characterized in that: The graphene has a purity of 99.9% and a specific surface area of 120 to 150 m 2 / g, the average flake thickness is 5 to 8 nm, and the average particle size is 5 to 10 μm.
10. Application of the graphene composite perovskite manganese oxide polycrystalline ceramic according to claim 1 in an uncooled infrared detector.
Citation Information
Cited By
Preparation method of nano Ag phase synergistic graphene composite perovskite manganese oxide ceramic
CN121085614A
Preparation method of nanometer Ag phase synergic graphene composite perovskite manganite ceramics
CN121085614B
Preparation method of porous LSMO heating body
CN121554276A
Preparation method of porous LSMO heating element
CN121554276B